Letter from James Curtis Booth to his brother-in-law, Conrad William Faber - Booth, James Curtis (1833)
Mentions translating portions of Jöns Jacob Berzelius' 1779-1848 Chemistry.
Keywords: Booth, James Curtis, 1810-1888; Berzelius, Jöns Jakob, friherre, 1779-1848